Status Gizi dan Prestasi Belajar Siswa Kelas 4-6 di SD GMIT Oeltua Kabupaten Kupang - Meltica Eonike Bani; Utma Aspatria; Tasalina Gustam (Yayasan Literasi Sains Indonesia, 2025)
Optimal growth and development in school-aged children are influenced by the provision of nutrition with appropriate quality and quantity. A balanced nutritional status, particularly during elementary school years, plays a critical role in supporting concentration, memory, and comprehension in the learning process. Poor nutritional status can lead to decreased academic achievement due to impaired cognitive and physical functions. Suboptimal brain development significantly affects students' learning abilities at school and may reduce productivity and creativity in adulthood.This study aims to examine the relationship between nutritional status and academic performance among students at GMIT Oeltua Elementary School, Taebenu Subdistrict, Kupang Regency. This research employed a quantitative method with a cross-sectional approach. The study population consisted of all students in grades 4 to 6 at GMIT Oeltua Elementary School, totaling 96 students (total sampling). Data were analyzed using the chi-square test with the SPSS 29.0 application. The results showed that there was no significant relationship between nutritional status (weight-for-height) and academic performance, with a p-value of 0.727 (p > 0.05).